2020
DOI: 10.1126/sciadv.aba8272
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft observations since the 1990s reveal increases of tropospheric ozone at multiple locations across the Northern Hemisphere

Abstract: Tropospheric ozone is an important greenhouse gas, is detrimental to human health and crop and ecosystem productivity, and controls the oxidizing capacity of the troposphere. Because of its high spatial and temporal variability and limited observations, quantifying net tropospheric ozone changes across the Northern Hemisphere on time scales of two decades had not been possible. Here, we show, using newly available observations from an extensive commercial aircraft monitoring network, that tropospheric ozone ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
141
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(152 citation statements)
references
References 77 publications
(97 reference statements)
7
141
4
Order By: Relevance
“…2018, M. Li, Liu, et al., 2017; Zheng, Chevallier et al., 2018; Zheng, Tong et al., 2018). However, ozone concentrations have worsened recently in China and it remains an important issue (Lu et al., 2018, 2020). Meanwhile, emissions in India and other South Asia regions have continued to grow (Koplitz et al., 2017; Kumar et al., 2018; C. Li, McLinden et al., 2017), and emissions from Africa are expected to accelerate (Liousse et al., 2014).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2018, M. Li, Liu, et al., 2017; Zheng, Chevallier et al., 2018; Zheng, Tong et al., 2018). However, ozone concentrations have worsened recently in China and it remains an important issue (Lu et al., 2018, 2020). Meanwhile, emissions in India and other South Asia regions have continued to grow (Koplitz et al., 2017; Kumar et al., 2018; C. Li, McLinden et al., 2017), and emissions from Africa are expected to accelerate (Liousse et al., 2014).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Here we build on our previous study (Zhang et al, 2016) by investigating how emission changes from different world regions, as well as the global methane concentration changes, have contributed to global B O3 changes (ΔB O3 ) from 1980 to 2010. We are particularly interested in quantifying the contributions of emissions from tropical and subtropical regions including Southeast Asia, South Asia, and Central and South America, as models and observations now suggest that tropospheric ozone is increasing fastest over these regions (Gaudel et al, 2018(Gaudel et al, , 2020. We also calculate B O3 changes from multimodel experiments from the second phase of the Task Force on Hemispheric Transport of Air Pollutants (HTAP2; Galmarini et al, 2017), which have not been reported previously, to investigate the sensitivity of B O3 to emissions from different world regions.…”
mentioning
confidence: 99%
“…Thus, they can only reflect the lower free tropospheric O 3 , and their longterm trends can be influenced by the signal of the European PBL air masses. Indeed, despite what was observed at the European mountain sites, by exploiting the IAGOS (In-Service Aircraft for a Global Observing System) database (Petzold et al, 2015), Gaudel et al (2020) reported an increase in median O 3 over Europe from 1 to 3 ppb/decade from the lower to the free troposphere between 1994 and 2016.…”
Section: Introductionmentioning
confidence: 89%
“…Trace gas or thermodynamic properties on adjacent pressure or altitude levels are often correlated, and the treatment of the levels as independent time series ignores the potential vertical interconnection. In order to reduce the estimation uncertainty of a trend on a particular level, methods have been developed that produce an area average from multiple time series in close spatial proximity (Wigley et al, 1984;Chang et al, 2017) or that employ a dimension reduction technique (e.g., principal component analyses) to project multiple layers of data into a reduced set (Ghil et al, 2002;Meiring, 2007;Park et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of such aggregations, either through averaging or dimension reduction, is to enhance a certain common underlying signal (or signals) or to produce regional means (Wigley et al, 1984;Ghil et al, 2002). While the issue of spatial irregularity can now be tackled by a wide range of sophisticated spatial interpolation techniques (Stein, 1999), the averaging approach has not been thoroughly investigated in an objective manner with respect to enhancing the signal-to-noise ratio.…”
Section: Introductionmentioning
confidence: 99%